KINERJA INVESTASI JASA PENGUJIAN TABLEWARE UNTUK PRODUK KREATIF KERAMIK PADA BTIKK-BPPT - Normal, I Nyoman (Jurnal Keuangan dan Perbankan, 2017)
The aims of this research were to analyze the tableware testing service investment, especially on ceramic glaze for eating and drinking equipment at BTIKK-BPPT. The analysis techniques used were payback period, net present value, profitability index, internal rate of return, and break-even point. The research results shew that the expansion investment of tableware testing service of ceramic on glaze for eating and drinking equipments qualified by BSN according to SNI 7275:2008 was feasible to be acted or applicated because they fulfilled the criteria of investment feasibility valuation, namely: payback period analysis result was 4,65 years, in which its value was shorter than range time of investment that was 10 years; net present value analysis resultÂ  was IDR.206.043.764,69, in which it was the positive value; profitability index analysis result wasÂ  1,41, in which its value was over than 1,00; internal rate of return analysis result was 18,93%, in which its value was over than 10,00%; and break-even point analysis resulted in 2.567,56 samples unit or IDR.256.911.104,11, in which it was smaller than 6.300,00 samples unit or IDR.783.000.000,00. For all criteria, the analysis of testing service investment (appearance, glazur hardness, temperature frightened tenacity, water absorption, Cd Pb solubility, glaze crack tenacity, and strike sturdy) was feasible to continue.